Persuasive Strategies Used by Kohcun and Mami Louisse on TikTok Live - Tabita Aurellia Anam; Ivonne Muliawati Harsono (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study discusses the persuasive strategies used by Kohcun and Mami Louisse on TikTok Live, using the theory of persuasive strategies by Beebe and Beebe (2018). This qualitative study analyzes transcripts from TikTok Live. The persuasive strategies that were present were inductive reasoning, causal reasoning, credible evidence, new evidence, specific evidence, evidence for a diverse audience, concrete examples, emotion-arousing words, fear appeals, and appeal to emotion of hope. This study also discusses the similarities and differences. The findings reveal that some strategies were used by both affiliators, some were not used by either, and the rest was used by one of the two affiliators. Although both affiliators employed multiple strategies in one utterance, Kohcun used multiple strategies more frequently and used the emotion-arousing words differently. Finally, the two affiliators employed different strategy combinations. The outcome of this study shed a spotlight on effective persuasive strategies for TikTok Live.